Advances in Photovoltaics. Part 3 - Willeke, G., 1954-; Weber, Eicke R. (Semiconductors and semimetals, 2014)
This volume is the third of a set of seven on the topic of photovoltaics. Solar cell-related technologies covered here include: ribbon silicon; heterojunction crystalline silicon; wafer equivalent crystalline silicon; and other advanced silicon solar cell structures and processes. Semiconductors and Semimetals has distinguished itself through the careful selection of well-known authors, editors, and contributors. Originally widely known as the ""Willardson and Beer"" Series, it has succeeded in publishing numerous landmark volumes and chapters. The series publishes timely, highly relevant v